1994
DOI: 10.1093/clinids/18.5.755
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Susceptibility of Tuberculosis in New York City, 1987-1991

Abstract: The annual number of cases of tuberculosis in New York City has increased since 1978. In addition, in 1991 a 1-month survey of cases of tuberculosis in New York City found that 33% of all cases were resistant to at least one drug. To determine susceptibility trends from 1987 to 1991, a period during which an unprecedented rise in resistant tuberculosis occurred in New York City, we reviewed the microbiology records of 44 New York City hospitals (comprising > 14,000 cases). The percentage of cases resistant to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…We further demonstrated that the E540V amino acid substitution influenced the interaction between DNA gyrase and the substituent(s) at R-7, R-8, or both in quinolone structures. This is the first detailed study of the contribution of the E540V amino acid substitution in GyrB to quinolone resistance in M. tuberculosis.A major human infectious disease, tuberculosis (TB) is estimated to affect approximately one-third of the world's population, and 95% of cases occur in developing countries (15,30,31). Current estimates show that approximately 9.4 million new cases and nearly 1.7 million deaths from TB occur each year, and TB remains a major cause of premature death (36).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We further demonstrated that the E540V amino acid substitution influenced the interaction between DNA gyrase and the substituent(s) at R-7, R-8, or both in quinolone structures. This is the first detailed study of the contribution of the E540V amino acid substitution in GyrB to quinolone resistance in M. tuberculosis.A major human infectious disease, tuberculosis (TB) is estimated to affect approximately one-third of the world's population, and 95% of cases occur in developing countries (15,30,31). Current estimates show that approximately 9.4 million new cases and nearly 1.7 million deaths from TB occur each year, and TB remains a major cause of premature death (36).…”
mentioning
confidence: 99%
“…A major human infectious disease, tuberculosis (TB) is estimated to affect approximately one-third of the world's population, and 95% of cases occur in developing countries (15,30,31). Current estimates show that approximately 9.4 million new cases and nearly 1.7 million deaths from TB occur each year, and TB remains a major cause of premature death (36).…”
mentioning
confidence: 99%
“…At the time the second Wolfheze Workshop took place, the AIDS epidemic had risen rapidly, impacting tangibly on TB morbidity in the US since 1985 [8]. The co-epidemic of multidrug-resistant (MDR)-TB in New York City (NY, USA) [9] made the front page of newspapers and drew the attention of politicians once again to TB. This US experience was widely presented to the participants in the second Wolfheze Workshop.…”
Section: Periodmentioning
confidence: 99%
“…In New York wurde in einer Prävalenzuntersuchung in 33 % aller Tuberkulosefälle eine Einfachresistenz, in 19 % eine Resistenz gegen Isoniazid und Rifampicin nachgewiesen [24]. Bei vorbehandelten Patienten waren 44 % der isolierten Erreger resistent gegen mindestens eines der getesteten Substanzen [52].…”
Section: Resistenzunclassified